Comunicación asertiva y su impacto en los ambientes virtuales con estudiantes de la Universidad Técnica de Babahoyo Extensión Quevedo año 2021 - Moyano Carbo, Piedad del Carmen (2021)
This Project intends that good communication practices entail a comprehensive, systematic training that seeks the differentiated change of the student within the classroom and professional training, it seeks to provide the elements to educators so that the teaching-learning process in which the student is part active, dynamic, and transforming of a new process, guided, controlled, and supervised by the teacher, who, based on their own communicative styles in their students, from the implementation of didactic strategies, that promote constant interaction, and the development of teamwork, which will develop greater motivation, and guarantee the process of teaching-learning and professional training of students, It will also allow students to be responsible and get involved in a systemic and problematic way in the process of transformation and development, which allows motivating all students, through the selection of texts that consolidate their professional training, maintaining assertive communication inside and outside the classroom. Today the new styles and transformations based on the scientific and methodological, seek a new path to development and demand from society and students, environments where their fundamental role search for alternatives and solutions to problems, which lead to educational work is developmental and multidisciplinary.